Encountering the other in literature: The Borges face to face - Abreu, Rosangela Costa de; Capaverde, Tatiana da Silva (Research, Society and Development, 2024)
In Comparative Literature, the relationships between authors and works do not start from the original-copy dichotomy, because just as the role of the author and the artistic work itself has been modified over time, the way in which writing and reading are correlated has undergone a reevaluation. In this way, textual creation is understood as dependent on transit in foreign libraries, which allows textual elements to be appropriated and given new meanings within the new context of production. Thus, the present work, carried out using the qualitative bibliographic methodology of Comparative Literature, aims to discuss the appropriation of the authorial image of Jorge Luís Borges by the author Antônio Fernando Borges in the short story Com toda certeza, quem sabe. Studies by Namorato (2011), Bakhtin (2022), Jobim (2020), among others, were used as theoretical support. The result was the understanding that through inclusion in someone else’s library, an author-reader can be classified as a literary anthropophagist, since he carries out processes of swallowing the artistic food of his predecessor to construct his writing, which is distinct and, at the same time, time, close to the other for aesthetic and authorial reasons. In view of this, it was concluded that by resuming Borgean writing techniques, as is the case of (self) fictionalization, Antônio Fernando Borges inserts himself in literature as an author-reader than Jorge Luis Borges and also as a propagator of the echoing literary voice by the argentine author.